Cytoskeletal actin dynamics shape a ramifying actin network underpinning immunological synapse formation - Fritzsche, Marco; Fernandes, Ricardo A.; Chang, Veronica T.; Colin-York, Huw; Clausen, Mathias P.; Felce, James H.; Galiani, Silvia; Erlenkämper, Christoph; Santos, Ana M.; Heddleston, John M.; Pedroza-Pacheco, Isabela; Waithe, Dominic; et al. (Science advances, 2017)
Activating T cells reorganize their cortical actin to form a ramified transportation network beneath the immunological synapse. T cell activation and especially trafficking of T cell receptor microclusters during immunological synapse formation are widely thought to rely on cytoskeletal remodeling. However, important details on the involvement of actin in the latter transport processes are missing. Using a suite of advanced optical microscopes to analyze resting and activated T cells, we show that, following contact formation with activating surfaces, these cells sequentially rearrange their cortical actin across the entire cell, creating a previously unreported ramifying actin network above the immunological synapse. This network shows all the characteristics of an inward-growing transportation network and its dynamics correlating with T cell receptor rearrangements. This actin reorganization is accompanied by an increase in the nanoscale actin meshwork size and the dynamic adjustment of the turnover times and filament lengths of two differently sized filamentous actin populations, wherein formin-mediated long actin filaments support a very flat and stiff contact at the immunological synapse interface. The initiation of immunological synapse formation, as highlighted by calcium release, requires markedly little contact with activating surfaces and no cytoskeletal rearrangements. Our work suggests that incipient signaling in T cells initiates global cytoskeletal rearrangements across the whole cell, including a stiffening process for possibly mechanically supporting contact formation at the immunological synapse interface as well as a central ramified transportation network apparently directed at the consolidation of the contact and the delivery of effector functions.